RAPID AND SIMPLE DETERMINATION OF PLASMA AMINO ACID RATIO - K. Montazemi; Sh. Hedayat; G. Rohani; S. Vafi (Tehran University of Medical Sciences, 1976)
In recent years considerable interest has been focused on the plasma amino acid patterns as a possible index of protein malnutrition, in children. Thus a change in the ratio of non-essential to essential amino acids is considered to be significant in the development of protein malnutrition. The present paper reports a simplified and rapid chromatographic procedure for the determination of this ratio. Plasma is mixed with ethyl alcohol and then centrifuge. The clear supernatant is applied directly to the paper. By the present technique the working time required for the chromatography reduced.